Answer:
-6 +2 = -4
Step-by-step explanation:
Its simple. Whenever you see two negative signs next to each other, they merge into an addition sign "positive".
-6+2 = -4
Answer:
x = 7
y = 12
Step-by-step explanation:
To do this question you have to know your exponent rules, but also you need to know how to add fractions.
To multiply
6^(1/3) × 6^(1/4)
you can keep the 6 and just add the exponents.
That's why the answer is set up on the form 6^(x/y)
To add fractions, you need a common denominator, it is 12.
1/3 is 4/12.
1/4 is 3/12.
So 1/3 + 1/4
is the same as:
4/12 + 3/12
= 7/12
7/12 is the exponent you are looking for.
x = 7 and y = 12.
6^(1/3) × 6^(1/4)
=6^(7/12)
Answer:
Solving the given formula for v2 gives us:
![a(t_2-t_1)+v_1 = v_2](https://tex.z-dn.net/?f=a%28t_2-t_1%29%2Bv_1%20%3D%20v_2)
Step-by-step explanation:
Solving an equation for a particular variable means that the variable has to be isolated on one side of the equation.
Given equation is:
![a = \frac{v_2-v_1}{t_2-t_1}](https://tex.z-dn.net/?f=a%20%3D%20%5Cfrac%7Bv_2-v_1%7D%7Bt_2-t_1%7D)
Multiplying both sides by t2-t1
![(t_2-t_1) . a = \frac{v_2-v_1}{t_2-t_1} . (t_2-t_1)\\a(t_2-t_1) = v_2-v_1](https://tex.z-dn.net/?f=%28t_2-t_1%29%20.%20a%20%3D%20%5Cfrac%7Bv_2-v_1%7D%7Bt_2-t_1%7D%20.%20%28t_2-t_1%29%5C%5Ca%28t_2-t_1%29%20%3D%20v_2-v_1)
Adding v1 to both sides of the equation
![a(t_2-t_1)+v_1 = v_2-v_1+v_1\\a(t_2-t_1)+v_1 = v_2](https://tex.z-dn.net/?f=a%28t_2-t_1%29%2Bv_1%20%3D%20v_2-v_1%2Bv_1%5C%5Ca%28t_2-t_1%29%2Bv_1%20%3D%20v_2)
Hence,
Solving the given formula for v2 gives us:
![a(t_2-t_1)+v_1 = v_2](https://tex.z-dn.net/?f=a%28t_2-t_1%29%2Bv_1%20%3D%20v_2)
Answer:
x = -7
Step-by-step explanation:
you have to distribute the 2 to what is in the parenthesis, then you get left with 2x+18=4 so subtract the 18 from both sides leaving you with 2x=-14 so you divide both by 2 leaving you with x=-7.